2020
DOI: 10.3390/w12010299
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Temporal Scales Assessment in the Hydrological Response of Small Mediterranean-Climate Catchments

Abstract: Mediterranean-climate catchments are characterized by significant spatial and temporal hydrological variability caused by the interaction of natural as well human-induced abiotic and biotic factors. This study investigates the non-linearity of rainfall-runoff relationship at multiple temporal scales in representative small Mediterranean-climate catchments (i.e., <10 km2) to achieve a better understanding of their hydrological response. The rainfall-runoff relationship was evaluated in 43 catchments at annua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Although no wide consensus has been established with regard to the questions posed in this work, we believe that there is a favorable perspective for this, which is justified by the recent intensification of related research efforts worldwide (e.g., [69][70][71][72], to mention but a few.) Additionally, one should not lose sight of the fact that many anthropogenic influences act simultaneously (e.g., forest fires, deforestation, large-scale hydraulic works) and affect the same hydrological variables by: (i) altering the rate of evaporation, (ii) modifying the velocity and amount of overland flow, (iii) altering the amount of infiltration into the ground, and (iv) affecting the amount of intercepted water [73].…”
Section: Discussionmentioning
confidence: 95%
“…Although no wide consensus has been established with regard to the questions posed in this work, we believe that there is a favorable perspective for this, which is justified by the recent intensification of related research efforts worldwide (e.g., [69][70][71][72], to mention but a few.) Additionally, one should not lose sight of the fact that many anthropogenic influences act simultaneously (e.g., forest fires, deforestation, large-scale hydraulic works) and affect the same hydrological variables by: (i) altering the rate of evaporation, (ii) modifying the velocity and amount of overland flow, (iii) altering the amount of infiltration into the ground, and (iv) affecting the amount of intercepted water [73].…”
Section: Discussionmentioning
confidence: 95%
“…This is a topic recently discussed by several scholars who paid attention to the intensification of fruit plantations (tropical and citrus orchards) and high soil and water losses due to bare soils, intense tillage practices and the use of pesticides (Rodrigo-Comino et al, 2020). Similar land-use trends, especially related to agricultural abandonment, are identified in numerous Mediterranean and semi-arid regions globally (Jenicek, 2009;Pérez-González et al, 2017;Hu and Shrestha, 2020;Fortesa et al, 2020). The main causes can be related to aging and depopulation of rural areas (Carbonaro et al, 2018;Pineda, 2001) and less productivity of cultivated lands affected by less fertile and productive soils affected by soil erosion processes (Novara et al, 2016;Rodrigo-Comino, 2018;Romero-Díaz et al, 2017;Lasanta et al, 2021).…”
Section: Land-use Changes and Curve Number Variationsmentioning
confidence: 86%
“…At the small-catchment scale, studies worldwide have demonstrated that vegetation established after land abandonment noticeably reduces runoff coefficients and is a major factor affecting flood control (e.g. [34][35][36][37][38]). Some of these studies have shown that revegetation also affects flood hydrograph characteristics, with lower peakflows, slower response times and slower recession limbs in forested catchments [39,40].…”
Section: Brief Review Of the Main Impacts Of Farmland Abandonment On mentioning
confidence: 99%